ANALISIS PROGRAM PEMBELAJARAN PAKET C DI UNIT PELAKSANA TEKNIS SATUAN PENDIDIKAN NONFORMAL - Harmayanti Harmayanti; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
Equality Education Package C is an Education program service through non-formal education channels aimed at people who have dropped out of school at the SMA/MA/SMK level, people who graduate from Package B and students who graduate from SMP/MTs. This study aims to: 1). To find out how the process of implementing the Package C program at UPT SPNF SKB. 2) To find out what factors affect the learning of the Package C program at UPT SPNF SKB. This study uses a descriptive qualitative approach. The research subjects were the head of the UPT SPNF SKB Institute, civil servant teachers and learning residents. Data collection techniques were carried out by interview, observation and documentation. Data analysis techniques used data editors, data presentation, and drawing conclusions. The data validity technique uses credibility (trust). The research results of the package C learning program show that: 1. The implementation of the package C learning program which includes: a) The planning carried out is the preparation of the curriculum, lesson plans, provision of facilities and infrastructure, sources of funds, tutors and students. b) The implementation of learning package C is carried out every Monday to Friday, taking place according to the plans and goals that have been set. c) evaluation is done by giving daily tests to students. 2. The supporting and inhibiting factors include: a) the supporting factors in learning package C are the existence of financial assistance from the government and the formal school building that is used as a place of learning. b) the inhibiting factor in learning package C is the presence of learning residents and the lack of approach between tutors and learning residents. The supervisor from the Education Office should evaluate UPT SPNF SKB to find out the success and failure of the package C program. And also to evaluate whether there are any obstacles faced by the UPT SPNF SKB during the implementation of the package C program. Tutors should also provide motivation to learning residents so that their attendance can be further improved